Deixis Found in We Can Be Heroes Movie - Upadani, Ida Ayu Agung Kardina; Artawa, Ketut; Parthama, I Gusti Ngurah (ANFA MEDIATAMA, 2024)
This research is carried out to get a depth-understanding of deixis usage found in Movie. The data of this research was taken from We Can Be Heroes movie by Robert Rodriguez that, released on December 25, 2020. The data for this research was collected using the documentation method. There are several steps to collect the data. First, download the movie transcript. Second, watching the movie repeatedly in order to find the utterances that contained deixis in the movie. Third, taking note and marking all data found, which contain the types of deixis. Lastly, analyse the types of deixis used in the movie. The data that have been collected are analyzed based on the deixis theory proposed by Levinson. The result showed that there are 419-person deixis, 44 place deixis, 50 temporal deixis, 142 discourse deixis, and 64 social deixis. Based on 719 data, the most dominant types of deixis that used in movie is person deixis.